2018
DOI: 10.18011/bioeng2018v12n4p327-332
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica Da Temperatura Da Pele De Equinos Durante Atividade Física Por Meio Da Termografia Infravermelha

Abstract: O objetivo foi descrever as mudanças na temperatura da pele de equinos durante o exercício obtido através da termografia infravermelha, bem como avaliar a funcionamento dos grupos musculares em resposta a atividade física. Foram utilizados dez equinos atletas da raça Quarto de Milha, delineados em parcelas subdivididas, resultando em dez repetições por tratamento. Os tratamentos consistiram das avaliações termográficas da temperatura da pele (Tp) dos cavalos em repouso (MR) e em dois momentos durante o exercíc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The increase in stifle temperatures in the EP1, after exercising on the VP at different intensities, suggests that the activity on the VP in this EP was performed on the pelvic musculature and on the stifle. This was also observed by Sala et al (2012) and Oliveira et al (2018) who used equine athletes to demonstrate increased temperature in the major muscle groups of the pelvic limbs.…”
Section: Discussionsupporting
confidence: 67%
“…The increase in stifle temperatures in the EP1, after exercising on the VP at different intensities, suggests that the activity on the VP in this EP was performed on the pelvic musculature and on the stifle. This was also observed by Sala et al (2012) and Oliveira et al (2018) who used equine athletes to demonstrate increased temperature in the major muscle groups of the pelvic limbs.…”
Section: Discussionsupporting
confidence: 67%
“…Although some authors reported significant temperature increases in hindlimb muscle surface right after different exercises (Simon et al, 2006;Yarnell et al, 2014;Gerardi, et al, 2019), others could not detect forelimb muscle temperature variation in Quarter horses (Oliveira et al, 2018).…”
mentioning
confidence: 91%